Product Selection and Components Replenishment Model of ATO Manufacturer under Heterogeneous Demand - Yuyu Li; Bo Huang (Journal of Applied Mathematics)
How to satisfy customers’ heterogeneous demands by limited models of product is the key problem in an ATO (Assemble-to-Order) manufacturer’s operations management. Based on the condition that customers’ demands depend on their types which follow uniform distribution, we develop an inventory model to study how an ATO manufacturer selects the products from the candidate products in a same product family and determines components replenishment quantities, in order to maximize its profit. We get the optimal set of products which an ATO manufacturer should assemble, as well as the components replenishment quantities through theoretical, numerical, and case analyses. Furthermore, we propose an algorithm to obtain the optimal solution on the set of products and the components replenishment quantities. We found that an ATO manufacturer should make the performance and qualities of products over a certain level, and determine the optimal selling duration of products according to their selling prices and qualities, as well as the purchase prices and holding costs of their components. This paper offers consultation for ATO manufacturers to make policies on product selection and components replenishment.